2010
DOI: 10.1074/jbc.m110.102434
|View full text |Cite
|
Sign up to set email alerts
|

Whole Body Deletion of AMP-activated Protein Kinase β2 Reduces Muscle AMPK Activity and Exercise Capacity

Abstract: AMP-activated protein kinase (AMPK) ␤ subunits (␤1 and ␤2) provide scaffolds for binding ␣ and ␥ subunits and contain a carbohydrate-binding module important for regulating enzyme activity. We generated C57Bl/6 mice with germline deletion of AMPK ␤2 (␤2 KO) and examined AMPK expression and activity, exercise capacity, metabolic control during muscle contractions, aminoimidazole carboxamide ribonucleotide (AICAR) sensitivity, and susceptibility to obesity-induced insulin resistance. We find that ␤2 KO mice are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

16
139
6

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 146 publications
(165 citation statements)
references
References 63 publications
16
139
6
Order By: Relevance
“…Furthermore, human trials have offered little evidence of a beneficial cardiac effect of sildenafil treatment in adults with DMD or Becker muscular dystrophy (58,59). In light of our findings, it is possible that the shortcomings of these previous studies reflect the existence of other functional targets of muscle-derived NO, or additional targets of altered AMPK regulation, that contribute to dysfunction in dystrophic muscle (43,60,61). This possibility warrants further investigation into whether acute AMPK activation can yield therapeutic benefit to dystrophic patients through the restoration of heart or skeletal muscle NO signaling.…”
Section: Discussioncontrasting
confidence: 50%
“…Furthermore, human trials have offered little evidence of a beneficial cardiac effect of sildenafil treatment in adults with DMD or Becker muscular dystrophy (58,59). In light of our findings, it is possible that the shortcomings of these previous studies reflect the existence of other functional targets of muscle-derived NO, or additional targets of altered AMPK regulation, that contribute to dysfunction in dystrophic muscle (43,60,61). This possibility warrants further investigation into whether acute AMPK activation can yield therapeutic benefit to dystrophic patients through the restoration of heart or skeletal muscle NO signaling.…”
Section: Discussioncontrasting
confidence: 50%
“…This can be explained by the importance of heterotrimeric complex in the stabilization of individual AMPK subunit. AMPK is stable as a heterotrimer complex, whereas each of its subunits is subject to an increased turnover rate and is depleted from the cell when not associated with others (41)(42)(43). Therefore, the observed higher expression of AMPK␤1 in AMPK␣ Ϫ/Ϫ MEFs indicates that the transduction of the Ad-DN resulted in an increase in the AMPK heterotrimer complex in the cell.…”
Section: Discussionmentioning
confidence: 85%
“…Previous studies have reported that voluntary running was decreased in both mhLKB1-KO and AMPK-DN mice (14,33,51,57). To investigate the effect of skeletal muscle-specific reduction of LKB1 or AMPK activity on exercise capacity, we compared the exercise capacities of LKB1-DN and AMPK-DN mice.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, skeletal muscle AMPK activity is required for maintaining exercise capacity. Several studies have demonstrated that exercise capacity is reduced dramatically in a skeletal musclespecific AMPK-deficient mice (14,33,51). However, more experiments have now demonstrated that skeletal muscle AMPK is dispensable in modulating the effects of contraction or pharmacological activation on fuel metabolism, raising the possibility that AMPK-independent pathways may regulate glucose and lipid metabolism (2,11,13,26,28,33,37).…”
mentioning
confidence: 99%